2013
DOI: 10.1371/journal.pgen.1003823
|View full text |Cite
|
Sign up to set email alerts
|

Both Rare and De Novo Copy Number Variants Are Prevalent in Agenesis of the Corpus Callosum but Not in Cerebellar Hypoplasia or Polymicrogyria

Abstract: Agenesis of the corpus callosum (ACC), cerebellar hypoplasia (CBLH), and polymicrogyria (PMG) are severe congenital brain malformations with largely undiscovered causes. We conducted a large-scale chromosomal copy number variation (CNV) discovery effort in 255 ACC, 220 CBLH, and 147 PMG patients, and 2,349 controls. Compared to controls, significantly more ACC, but unexpectedly not CBLH or PMG patients, had rare genic CNVs over one megabase (p = 1.48×10−3; odds ratio [OR] = 3.19; 95% confidence interval [CI] =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 67 publications
4
58
0
Order By: Relevance
“…Additionally, we demonstrate that Fgf8 is a crucial ligand signaling upstream of the Mapk pathway to induce astroglial differentiation via the pro-astrogliogenic transcription factors Nfia and Nfib. Taken together, our findings elucidate a key cellular mechanism that reconciles the relationship between delayed astroglial development and callosal agenesis, and are consistent with previous observations following mouse or human mutations in either Fgf signaling genes or Nfi genes (Barton et al, 1995; Chen et al, 2011; Dode and Hardelin, 2009; Dode et al, 2003; Ji et al, 2014; Koehler et al, 2010; Lajeunie et al, 1999; Li et al, 2012; Lu et al, 2007; McCabe et al, 2011; Piper et al, 2009a; Rao et al, 2014; Raybaud and Di Rocco, 2007; Sajan et al, 2013; Shu et al, 2003a; Sivasankaran et al, 1997; Smith et al, 2006; Steele-Perkins et al, 2005; Stewart et al, 2016; Tokumaru et al, 1996; Wilkie et al, 1995). …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Additionally, we demonstrate that Fgf8 is a crucial ligand signaling upstream of the Mapk pathway to induce astroglial differentiation via the pro-astrogliogenic transcription factors Nfia and Nfib. Taken together, our findings elucidate a key cellular mechanism that reconciles the relationship between delayed astroglial development and callosal agenesis, and are consistent with previous observations following mouse or human mutations in either Fgf signaling genes or Nfi genes (Barton et al, 1995; Chen et al, 2011; Dode and Hardelin, 2009; Dode et al, 2003; Ji et al, 2014; Koehler et al, 2010; Lajeunie et al, 1999; Li et al, 2012; Lu et al, 2007; McCabe et al, 2011; Piper et al, 2009a; Rao et al, 2014; Raybaud and Di Rocco, 2007; Sajan et al, 2013; Shu et al, 2003a; Sivasankaran et al, 1997; Smith et al, 2006; Steele-Perkins et al, 2005; Stewart et al, 2016; Tokumaru et al, 1996; Wilkie et al, 1995). …”
Section: Discussionsupporting
confidence: 91%
“…Since human individuals with NFIA haploinsufficiency, as well as Nfia and Nfib knockout mice, exhibit callosal malformations (Chen et al, 2011; Lu et al, 2007; Piper et al, 2009a; Sajan et al, 2013; Shu et al, 2003a; Steele-Perkins et al, 2005), we sought to investigate whether Nfi transcription factors regulate callosal development via astroglial IHF remodeling. Examination of two cases of human NFIA and NFIB haploinsufficiency using structural MRI revealed that these individuals display abnormal retention of the IHF associated with callosal agenesis (Figure 6E).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because none of these tissues belong to the classic VATER/VACTERL organ systems, its involvement in expression of VATER/VACTERL phenotypes in human seems unlikely. However, recently, Sajan et al () identified an overlapping deletion on chromosomal region 5q23.1 in a patient with cerebellar hypoplasia. Therefore, it cannot be excluded, that the here‐observed deletion of chromosomal region 5q23.1 contributed to the expression of the VATER/VACTERL‐like phenotype in Patient 5.…”
Section: Resultsmentioning
confidence: 99%
“…Chromosome Xp22.3 deletion has been discovered in a boy with cerebral cortical heterotopias and mental retardation (van Steensel, Vreeburg et al 2008). While chromosome 8p21.1-q11.23 is linked to basal ganglia calcification (Dai, Gao et al 2010), 8p23.1-p11.1 duplications as well as 1p31.3-p31.1 deletions have been observed in patients with corpus callosum agenesis (Sajan, Fernandez et al 2013). Duplication of 15q has also been found in those with hippocampal dysplasia and heterotopias, hippocampal sclerosis and malformation, corpus callosum hypoplasia and thinning, as well as greater pericerebral spaces (Boronat, Mehan et al 2015).…”
Section: Sex Differences In the Neurogenetics Of Autismmentioning
confidence: 99%